Innovative algorithm for easing VIP's navigation by avoiding obstacles and finding safe routes - Dooraki A.R.; Hooshyar D.; Yousefi M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Big data; Bioinformatics; Computer vision; Image matching; Navigation; Obstacle detectors; Units of measurement; Autonomous Vehicles; Ground planes; Obstacle detection; RANSAC; Visually impaired persons; Algorithms